Chlorinated 2‐hydroxynaphthalenoxazolines: Synthesis, Reaction Mechanism and Fluorescence Properties. Issue 18 (7th November 2016) - Barbeiro, Cristiane S.; Vasconcelos, Stanley N. S.; Zukerman‐Schpector, Júlio; Caracelli, Ignez; Pimenta, Daniel C.; Rodrigues, Ana Clara B.; Fernandes, André S.; Correra, Thiago C.; Bastos, Erick L.; Stefani, Hélio A.
Abstract: A chlorinated 2‐HNO (2‐hydroxynaphthalenoxazoline) was synthesized by an ultrasound‐assisted coupling reaction between 1‐hydroxy‐2‐naphthoic acid and L‐threonine followed by simultaneous halogenation and cyclization with inversion of configuration using excess SOCl2 . Further functionalization of 2‐HNO led to a small library of slightly fluorescent amides or esters in 55–81 % yields. Quantum chemical calculations combined with high‐resolution mass spectrometry analysis were used to rationalize the mechanism of reaction, and the formation of SCl3 + as an electrophile is proposed. Abstract : 2‐oxazoline was synthesized by an ultrasound‐assisted coupling reaction between 1‐hydroxy‐2‐naphthoic acid and L‐threonine followed by simultaneous halogenation and cyclization with inversion of configuration using excess SOCl2 . Further functionalization of 2‐HNO led to a small library of slightly fluorescent compounds. Quantum chemical calculations combined with high‐resolution mass spectrometry analysis were used to rationalize the mechanism of reaction.